Functionally Small Riemann Sums (FSRS) Dan Essentially Small Riemann Sums (ESRS) Fungsi Terintegral Henstock-Kurzweil Dari Ruang Euclide R^n ke Ruang Barisan L^p - Aniswita Aniswita (Beta: Jurnal Tadris Matematika, 2010)
In this paper we discuss Fuctionally Small Riemann Sums (FSRS) properties end Essentially Small Riemann Sums (ESRS) properties for Henstock-Kurzweil integrable functions from the Euclidean spaces R^n into the Sequences space L^p